Contested Justice : The Politics and Practice of International Criminal Court Interventions - De Vos, Christian; Kendall, Sara; Stahn, Carsten (Cambridge : Cambridge University Press, 2015)
The International Criminal Court emerged in the early twenty-first century as an ambitious and permanent institution with a mandate to address mass atrocity crimes such as genocide and crimes against humanity. Although designed to exercise jurisdiction only in instances where states do not pursue these crimes themselves (and are unwilling or unable to do so), the Court's interventions, particularly in African states, have raised questions about the social value of its work and its political dimensions and effects. Bringing together scholars and practitioners who specialise on the ICC, this collection offers a diverse account of its interventions: from investigations to trials and from the Court's Hague-based centre to the networks of actors who sustain its activities. Exploring connections with transitional justice and international relations, and drawing upon critical insights from the interpretive social sciences, it offers a novel perspective on the ICC's work. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Open Access title.